Organizational Change : creating change through strategic communication - Lewis, Laurie (Hoboken : Wiley Blackwell, 2019)
"Collection of articles on behavior and organizational change from researchers at the University of the Basque Country"--Provided by publisher.
Introduction / Sabino Ayestaran and Jon Barrutia Guenaga -- Human resources and innovation a study of practices developed by innovative companies in the Basque Country / Ibon Zamanillo Elguezabal and Eva Velasco Balmaseda -- Vectors of organizational change in European Union company law / Juan Pablo Landa and Igone Altzelai -- CSR : company stakeholder responsibility / Jose Luis Retolaza, Leire San-Jose, and Andres Araujo de la Mata -- Origins and development of industrial clusters in the Basque Country : path dependency and economic evolution / Jesus Maria Valdaliso, Aitziber Elola, Maria Jose Aranguren, and Santiago Lopez -- Systemic and multilevel approach to organizational analysis / Nekane Balluerka -- How do cultural changes influence the psychological contract between worker and organization? / Jose Valencia Garate -- Leadership conduct and its consequences for organizations in the Basque Country / Juan Jose Arrospide, Daniel Hermosilla, Felix Yenes and Inigo Calvo -- Emotional intelligence and innovation : an exploratory study in organizational settings / Aitor Aritzeta -- List of contributors -- Index.
Includes bibliographical references and index.
Keywords: Organizational change -- Strategic communication